1987
DOI: 10.1159/000138309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphine on Gastric Ulceration, Barrier Mucus and Acid Secretion in Pylorus-Ligated Rats

Abstract: The effects of intraperitoneal (IP) or intracerebroventricular (ICV) administration of morphine on acid and pepsin secretion, gastric ulceration and gastric bound mucoproteins were investigated in pylorus-ligated rats. Morphine, administered IP, produced a dose-dependent inhibition of the gastric secretion volume, acidity, pepsin output and bound mucoproteins. By contrast, the effect of morphine on gastric ulcers was not dose-dependent: a significant increase in gastric lesions was obtained with morphine 5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Evidence indicating the involvement of opioid transmission to DMX, as a component of the dorsal vagal complex, originating from neurons of the NTS, amygdala or periaqueductal gray (Morilak et al 1989, Pickel et al 1989, Maley 1996, Farkas et al 1997, Giraudo et al 1998, Liubashina et al 2000 additionally support the functional significance of LENK related transmission in porcine DMX. In fact, activation of central opioid receptors have been shown to induce gastric relaxation (Burks et al 1987, Gue et al 1989, decrease gastric acid secretion (Del Tacca et al 1987) and increase feeding (Giraudo et al 1998). Identification of the close spatial relationship between LENK-IR processes and the preganglionic parasympathetic cell bodies shed light on its possible regulatory function in the porcine DMX.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicating the involvement of opioid transmission to DMX, as a component of the dorsal vagal complex, originating from neurons of the NTS, amygdala or periaqueductal gray (Morilak et al 1989, Pickel et al 1989, Maley 1996, Farkas et al 1997, Giraudo et al 1998, Liubashina et al 2000 additionally support the functional significance of LENK related transmission in porcine DMX. In fact, activation of central opioid receptors have been shown to induce gastric relaxation (Burks et al 1987, Gue et al 1989, decrease gastric acid secretion (Del Tacca et al 1987) and increase feeding (Giraudo et al 1998). Identification of the close spatial relationship between LENK-IR processes and the preganglionic parasympathetic cell bodies shed light on its possible regulatory function in the porcine DMX.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of mucus levels bound to the epithelial surface was performed according to the method of Come et al [17], as reported by Del Tacca et al [18]. Briefly, the glandular portion of the stomach was excised and immersed for 2 h in 0.1% Alcian blue in a 0.…”
Section: Evaluation O F the Adherent Gastric Mucusmentioning
confidence: 99%
“…Assessment of gastric acid secretion was carried out on pylorusligated rats, as previously reported by Del Tacca et al [18], with minor modifications.…”
Section: Evaluation O F Gastric Acid Secretionmentioning
confidence: 99%
“…Both central and peripheral effects may be involved in gastroprotective action of opioids against stress-or pylorus-ligation-induced mucosallesions [15,24,25]. However, gastric acid secretion is involved in the pathomechanism of both ulcer models.…”
Section: Introductionmentioning
confidence: 99%
“…However, gastric acid secretion is involved in the pathomechanism of both ulcer models. Since opioids exert inhibitory activity on gastric acid secretion injected either intracerebroventricularly (icv) or peripherally [24,26], the question was raisedwhether the antiulcer activity of opioids following icv administration is due to their antisecretory activity or whether their gastroprotective effect is independent of their antisecretory property. Therefore, in the present experimental series, we examined how opioids influence gastric lesions following icv administration in anulcermodel, where gastric acid secretion is not involved in the development of gastric mucosal lesions.…”
Section: Introductionmentioning
confidence: 99%